2017
DOI: 10.1007/s40544-017-0176-4
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of the coated and textured ring/liner conjunction based on a thermal mixed lubrication model

Abstract: For the ring/liner conjunction, well-designed surface texturing has been regarded as a potential means to improve its tribological performance, as well as the application of coating. However, so far most researchers focused on the one of these aspects. In this study, the combined effect of coating and texturing on the performance of ring/liner conjunction is numerically investigated. A thermal mixed lubrication model is presented. The effects of the coating's thermal and mechanical properties on the tribologic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
18
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 25 publications
(21 citation statements)
references
References 29 publications
(39 reference statements)
0
18
0
Order By: Relevance
“…In order to improve the properties of coatings and accelerate the innovation of materials, Chen et al [267][268][269] investigated the coating formation mechanism from a more microscopic perspective, including the particle in-flight status and droplet spreading process. Gu et al [270] analyzed the coated and textured ring/liner conjunction based on a thermal mixed lubrication mode. High velocity oxygen-fuel (HVOF) and high velocity air-fuel (HVAF) spraying techniques were used to deposit FeVCrCbased coatings to increase wear resistance of metals, and these coatings exhibited very low sliding wear rates [271].…”
Section: Hard Coatingsmentioning
confidence: 99%
“…In order to improve the properties of coatings and accelerate the innovation of materials, Chen et al [267][268][269] investigated the coating formation mechanism from a more microscopic perspective, including the particle in-flight status and droplet spreading process. Gu et al [270] analyzed the coated and textured ring/liner conjunction based on a thermal mixed lubrication mode. High velocity oxygen-fuel (HVOF) and high velocity air-fuel (HVAF) spraying techniques were used to deposit FeVCrCbased coatings to increase wear resistance of metals, and these coatings exhibited very low sliding wear rates [271].…”
Section: Hard Coatingsmentioning
confidence: 99%
“…In these works [13][14][15][16][17], the lubrication condition of the RLC was assumed to be fully flooded, and an isothermal condition was also considered. By considering that the oil film thermal effect caused by friction and the prevalent starved lubrication condition in an RLC, Meng and his coworkers [18][19][20] studied the effects of surface texture on the frictional characteristics of an RLC. Their results showed that surface texture can reduce the friction of an RLC significantly, even if the lubrication condition was starved.…”
Section: Of 21mentioning
confidence: 99%
“…Their results showed that surface texture can reduce the friction of an RLC significantly, even if the lubrication condition was starved. In the works of Meng et al [18][19][20], an ideal circular liner was considered to evaluate the frictional characteristics of a surface textured RLC.…”
Section: Of 21mentioning
confidence: 99%
See 2 more Smart Citations